Contemporary economics - McEachern, William A (Thomson South-Western, 2008)
Blends economic expertise and educational insights with comprehensive content, instructional design, and extensive print and media teaching tools. This edition includes two chapters covering personal finance, including information on managing money and being a responsible consumer.